City Tourism: National Capital Perspectives - Maitland, Robert (CABI, 2014)
Twenty years ago, Ashworth (1989) pointed to a double neglect of city tourism. Tourism researchers had neglected the city, though so much tourism took place there, and urbanists had neglected tourism, despite its rapid growth and increasing influence on cities. Much has changed. For developers and policy makers, city tourism is now mainstream, and no longer associated just with resorts and historic cities. Former industrial cities have taken to tourism as an important part of the way they must make their living in a changing world, and national capitals have given more attention to tourism. As is shown elsewhere in the book, national capitals have always had special qualities that attract visitors, but their attitudes towards tourism have at times been ambivalent. For example, London has long been a leading – on some measures, theleading – national capital destination, but until the 1980s city policy makers saw tourism primarily as a problem to be managed, while admitting some benefits, mainly to unskilled workers (e.g. Lipscomb and Weatheritt, 1977). For their part, tourists have shown an increasing desire to visit cities, as global tourism numbers have grown and trips have multiplied. Now as Fainstein et al. (2003, p. 8) say, ‘virtually every city sees a tourism possibility and has taken steps to encourage it’.